Analisis Kesalahan Siswa Kelas XI SMAN 1 Wolowa dalam Menyelesaikan Masalah Kontekstual Berkaitan dengan Program Linear Dua Variabel - Rahman, Muhamad; Lestari, Dian (Jurnal Akademik Pendidikan Matematika, 2023)
The formulation of the problem in this research is what errors are experienced by class variable. The aim of this research is to determine the errors of class XI students at SMAN 1 Wolowa in solving contextual problems related to two-variable linear programs and the factors that cause errors of class. This research is qualitative research with descriptive methods. The population of this research was class XI students of SMA Negeri 1 Wolowa with a total of 144 students and XI IPA 1 as research subjects. The instruments of this research are diagnostic tests and interview guidelines. The data collection techniques of this research are diagnostic tests and interviews. The data analysis techniques used are data reduction, data presentation, and data verification. The conclusions in this research is that 20 reading errors were caused by the inability to interpret keywords from the information contained in the problem, 33 comprehension errors were caused by a lack of accuracy in writing down what was known incompletely and incorrectly, 66 transformation errors were caused by the inability to transform the information, 83 errors on process skill are caused by errors in the steps used to solve the problem, errors in writing formulas, and errors in carrying out calculations, and 83 errors in writing the final answer are caused by students not being able to write the final results correctly with conclusions.